Ethics of Targeted Killings and Assassinations. (4th May 2022) - Koven, Steven G.; Perez, Abby F.
Abstract: Modern weaponry expedites the ability of actors in technologically advanced nations to eliminate real as well as perceived adversaries. Improved accuracy of unmanned aircraft (e.g., drones) reduces the risk of offensive action to active duty personnel and perhaps can lead to further acceptance of the assassination or targeted killing options. The killing of Iranian General Qasem Soleimani in 2020 as well as prior targeted killings refreshes an eternal debate relating to rules of engagement between adversaries in conflict. In an effort to contribute to the debate, this article (1) reviews historical positions on assassinations and targeting killings, (2) identifies linkages between ethics, assassinations and targeted killings, and (3) assesses the legal and ethical implications of assassination and targeted killing policies.